Sarcopenia as a predictor of postoperative complications in patients with pancreatic cancer - Kopchak , V.M.; Pererva, L.O.; Shkarban, V.P.; Trachuk, V.I.; Lynnyk, S.V. (Medicni Perspektivi, 2021)
Several studies showed that sarcopenia is associated with an increase of postoperative complications, with worse postoperative results in patients with pancreatic cancer. According to European Working Group on Sarcopenia, it is a "progressive and generalized skeletal muscle loss" characterized by both loss of skeletal muscle mass and strength (Cruz-Jentoft AJ et al., 2019). Aim of our work was to evaluate the effect of sarcopenia on the occurrence of postoperative complications after pancreatic resections in patients with pancreatic and periampullary cancer. We performed a retrospective analysis of treatment of 152 patients who underwent radical pancreatic resections. Sarcopenia was determined by preoperative computed tomography using the Hounsfield Unit Average Calculation (HUAC). In our investigation we measured the psoas area and density (Hounsfield Units) at the level of the third lumbar vertebral body (L3). Sarcopenia was diagnosed in 66 (43.4%) patients. Among patients with sarcopenia complications occurred in 41 (62.1%), mortality was 4 (6.1%). In the group of patients without sarcopenia, complications occurred in 29 (33.7%) of 86 patients, mortality was 2 (2.3%). The level of postoperative complications in patients with sarcopenia was significantly higher (c2 =12.1, p=0.0005). Postoperative mortality in patients with sarcopenia was higher without significant difference (c2 =1.3, p=0.24). Sarcopenia significantly affects the level of postoperative complications and its detection can be used to improve the selection of patients before pancreatic resections in patients with pancreatic cancer.